Knowledge, attitudes and practices of vape use among secondary school students: bridging awareness and behaviour - Siti Umairah, Mokhtar; Wan Norfazilah, Wan Ismail; Khairiah, Mohd Mokhtar; Nor Adila, Mhd Omar; Nurul Huda, Abu Bakar; Nurul Hidayah, Abu Bakar (Karya Ilham Publishing, 2025)
This study aims to investigate the knowledge, attitudes and practices (KAP) related to vaping among secondary school students in the Kuantan district, Pahang, Malaysia, considering the continued rise in usage and its health implications, despite widespread knowledge of the risks. A cross-sectional study was conducted from April to June 2024 in eight selected public secondary schools. A total of 431 students aged 13 to 17 completed a validated KAP questionnaire. Data were analysed using descriptive statistics, independent t-tests and Pearson correlation analysis in SPSS Version 21.0. 17.4% respondents reported being current vapersand65.2% had family members who smoked. Vapers exhibited significantly higher knowledge scores compared to non-vapers, despite holding more positive attitudes towards vaping. The Pearson correlation showed a moderate positive relationship between knowledge and attitude, suggesting that higher knowledge does not equate to more negative attitudes. Despite high knowledge of vaping risks, positive attitudes toward vaping persist among vapers. This suggests that knowledge alone is insufficient to change behaviour.